Problematika Penerimaan Peserta Didik Baru Melalui Jalur Penerimaan Vokasi Industri (JARVIS) di SMK SMAK Padang - Indri Astuti, Ismaya; Nasir, Nasir (Policy, Law and Political Research Center, 2023)
The implementation of new student admission curently is carried out online in most parts of Indonesia. Jalur Penerimaan Vokasi Industri (JARVIS) was initiated by the Ministry of Industry to meet the needs of the community, especially for prospective students so that they can choose and apply to schools or polytechnics under the auspices of the Industrial Human Resources Development Agency, Ministry of Industry. There are 3 pathways in online new student admission through JARVIS, namely Achievement, Independent and Together. JARVIS has made changes and impacts that make prospective registrants have flexible time in registering, but there are still some problems encountered during the JARVIS registration process. In this study, qualitative-descriptive methods were used to find out how the implementation of the New Student Admission process through JARVIS and to find out what problems were encountered during the implementation of Jarvis at Chemical Analyst Vocational School so that it could describe the reality and actual conditions of the implementation of JARVIS in depth.